2022
DOI: 10.7759/cureus.31892
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prevalence of the Use of Nasal Decongestants Among the General Population in Saudi Arabia

Abstract: BackgroundA topical nasal decongestant (NDC) is widely prescribed in ENT practice and used as self-medication because it is available over the counter, which makes it an easily accessible medication. Due to its common and long-term use, it is associated with serious nasal complications. It is commonly self-administrated in many otolaryngology diseases like the common cold, sinusitis, and acute or chronic rhinitis. The long-term usage of nasal decongestants is associated with significantly increased side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In the general population of Saudi Arabia, approximately 45.1% reported utilizing NDs. 12 Furthermore, within the participants of this study, around 15.0% indicated obtaining NDs through a prescription from a physician. However, although there exists a minority of physicians who prescribe these medications, it has been observed that they are the primary prescribers of NDs, constituting over half of the users, while pharmacists advise approximately one-fifth of the cases.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the general population of Saudi Arabia, approximately 45.1% reported utilizing NDs. 12 Furthermore, within the participants of this study, around 15.0% indicated obtaining NDs through a prescription from a physician. However, although there exists a minority of physicians who prescribe these medications, it has been observed that they are the primary prescribers of NDs, constituting over half of the users, while pharmacists advise approximately one-fifth of the cases.…”
Section: Discussionmentioning
confidence: 72%
“…However, although there exists a minority of physicians who prescribe these medications, it has been observed that they are the primary prescribers of NDs, constituting over half of the users, while pharmacists advise approximately one-fifth of the cases. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epi-Info (Centers for Disease Control and Prevention, Atlanta, GA, USA) was used to estimate the minimum sample size required for data collection. Based on the total population of Al-Qunfudah governorate (300,516) [ 11 ] and the frequency of nasal decongestants' utilization in Saudi Arabia (45.1%) [ 8 ], at CI (95%) and margin of error (5%), the minimum sample size was 380.…”
Section: Methodsmentioning
confidence: 99%
“…Nasal decongestants are commonly used and are easily accessible and available over the counter, but as before mentioned, they have many side effects [ 7 ]. A study from a large Saudi city, Jeddah, revealed that a significant percentage (over 50%) of adults used over-the-counter (OTC) medications in an improper and dangerous manner [ 8 ]. Additionally, few studies in Saudi Arabia detected inadequate knowledge about medication uses [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%